Pemberdayaan Komunitas Wisata Desa Melalui Manajemen Media Sosial Berbasis Data - Winata, Edi (Sekolah Tinggi Ilmu Manajemen Sukma Medan, 2025)
This community service program aims to improve digital literacy in the community through social media training, particularly for MSMEs. Based on an initial survey, participants had a high level of social media usage but did not fully understand content management strategies and the use of insight features. After the training, there was a significant increase in three key indicators: understanding of social media insights (from 70% to 93%), consistency of content uploads (from 40% to 68%), and audience interaction (up to 55%). These results demonstrate the success of this hands-on, participatory, and practice-based training approach. Comparison with recent research literature supports this finding, which suggests that digital training plays a crucial role in empowering MSMEs. However, this activity has limitations, including limited training time and varying levels of participant literacy. Follow-up programs and ongoing mentoring are recommended for optimal impact.